2015
DOI: 10.4049/jimmunol.1400169
|View full text |Cite
|
Sign up to set email alerts
|

Stable Interactions and Sustained TCR Signaling Characterize Thymocyte–Thymocyte Interactions that Support Negative Selection

Abstract: Negative selection is one of the primary mechanisms that render T cells tolerant to self. Thymic dendritic cells play an important role in negative selection, in line with their ability to induce migratory arrest and sustained T cell receptor (TCR) signals. Thymocytes themselves display self-peptide/MHC class I complexes, and while there is evidence that they can support clonal deletion, it is not clear whether they do so directly, via stable cell-cell contacts and sustained TCR signals. Here we show that muri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 47 publications
1
13
0
Order By: Relevance
“…DP thymocytes exhibited relatively random and slow migration with repeated migratory arrest. This intermittent deceleration of migration speed was associated with transient elevation of intercellular calcium concentration ([Ca 2+ ] i ) upon TCR engagement with self-peptide/MHC in a positively selecting environment (4,45), reminiscent of TCR stopping of mature T cells upon Ag recognition (46). Simultaneous imaging of thymocyte trafficking and Rap1 activation showed that normal cortical thymocytes exhibited migration with modest Rap1 activity.…”
Section: Discussionmentioning
confidence: 99%
“…DP thymocytes exhibited relatively random and slow migration with repeated migratory arrest. This intermittent deceleration of migration speed was associated with transient elevation of intercellular calcium concentration ([Ca 2+ ] i ) upon TCR engagement with self-peptide/MHC in a positively selecting environment (4,45), reminiscent of TCR stopping of mature T cells upon Ag recognition (46). Simultaneous imaging of thymocyte trafficking and Rap1 activation showed that normal cortical thymocytes exhibited migration with modest Rap1 activity.…”
Section: Discussionmentioning
confidence: 99%
“…It is not clear from the literature what role thymocytes play (as opposed to thymic stromal cells [TSC]: Brown, 2005; Melichar et al 2015) and which population(s) participate in responses to EDC. Data from chimeras (Staples et al 1999) suggest that ERα on stromal cells may be responsible for the decrease in thymic cellularity rather than ERα on thymocytes themselves.…”
Section: Discussionmentioning
confidence: 99%
“…The results thus cannot exclude a likelihood that TSC have a role in EDC-mediated toxicities in vivo (Kaplan et al 2015). Rather, it shows that in addition to potential TSC effects, EDC (like DES and HPTE) have direct effects on embryonic thymocytes similar to sustained thymocyte-thymocyte interactions that support negative selection (Melichar et al 2015). …”
Section: Discussionmentioning
confidence: 99%
“…1a). We used flow cytometry to determine the ratio of viable OT-93 I:reference thymocytes remaining in the slice as a measure of negative selection 94 10,20,21 (Fig. 1a).…”
mentioning
confidence: 99%
“…Although some non-phagocytic subsets, including mTECs, thymocytes, and B cells, 248 can induce negative selection 3,21,46 , this process may be rendered less efficient by 249 the requirement for a second cellular encounter with a phagocyte in order to 250 complete negative selection ( Supplementary Fig. 5b).…”
mentioning
confidence: 99%